High-elasticity hot melt adhesive film based on TPR material and preparation method of high-elasticity hot melt adhesive film
By using TPR material and modified talc powder in the hot melt adhesive film, the existing hot melt adhesive film has solved the problems of poor anti-aging performance and insufficient waterproof performance, and a hot melt adhesive film with high elasticity, excellent adhesive performance and waterproof performance is achieved.
Patent Information
- Application Number
- CN202411824567.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hot melt adhesive film has poor anti-aging performance under the action of heat, humidity and light, and the adhesive strength and cohesion strength are reduced, which affects the durability of use. At the same time, the waterproof performance needs to be improved.
TPR material is used as a key component, combined with modified talc powder, compatibilizer, tackifying resin and catalyst, to improve the elasticity, flexibility and adhesive properties of the hot melt adhesive film through specific preparation methods.
It significantly improves the elasticity, adhesion, anti-aging and waterproof properties of the hot melt adhesive film, extends its service life, and improves its stability in different environments.
Smart Images

Figure BDA0005183918380000031 
Figure BDA0005183918380000032 
Figure BDA0005183918380000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hot melt adhesive films, and in particular, relates to a high elastic hot melt adhesive film based on TPR material and a preparation method thereof. Background Art
[0002] In recent years, with the vigorous development of electronic products, construction industry, clothing decoration, footwear industry, automobile, household products and other industries, hot melt adhesive film, as a new type of adhesive, has been widely used due to its strong adhesion, no pollution, easy operation and storage. Hot melt adhesive film is generally prepared from saturated polyolefin materials as the base material, such as polyethylene (PE), ethylene-vinyl acetate copolymer (EVA), polyolefin elastomer (POE), etc. Hot melt adhesive film is a kind of hot melt adhesive.
[0003] TPR is a thermoplastic elastomer, which is based on thermoplastic styrene-butadiene rubber such as SBS (triblock copolymer of styrene and butadiene monomers) and SEBS (styrene-ethylene / butylene-styrene block copolymer), and is mixed with PP (polypropylene) and PS (polystyrene) resins, fillers, plasticizers and other functional additives to modify the material. TPR has excellent elasticity and softness. Adding it to hot melt adhesive film can make the hot melt adhesive film have better elasticity, flexibility and bonding properties. However, there is little research on adding TPR materials to hot melt adhesive film.
[0004] In addition, most of the hot melt adhesive films in the prior art have poor anti-aging performance. Under the action of heat, moisture and light, the adhesive strength and cohesive strength decrease significantly, which seriously affects the durability of the hot melt adhesive film. At the same time, the waterproof performance of the hot melt adhesive film in the prior art also needs to be improved. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a high elastic hot melt adhesive film based on TPR material and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A high elastic hot melt adhesive film based on TPR material comprises the following raw materials in parts by weight: 40-50 parts of ethylene-vinyl acetate copolymer, 25-35 parts of high density polyethylene, 10-15 parts of low density polyethylene, 2-5 parts of TPR, 5-15 parts of compatibilizer, 5-15 parts of tackifying resin, 1-3 parts of lubricant, 10-15 parts of modified talc powder and 0.01-0.1 parts of catalyst.
[0008] TPR has excellent elasticity and softness. Adding it to hot melt adhesive film can make the hot melt adhesive film have better elasticity, flexibility and bonding performance, which is suitable for application scenarios that require high elasticity and softness. In addition, TPR also has excellent wear resistance and anti-aging properties, which can extend the service life of hot melt adhesive film.
[0009] Furthermore, the compatibilizer is maleic anhydride grafted polyethylene.
[0010] Furthermore, the tackifying resin is one or more of hydrogenated petroleum resin, phenolic terpene resin, and C5 petroleum resin.
[0011] Furthermore, the lubricant is one or more of polyethylene wax, methyl silicone oil, and silicone resin.
[0012] Furthermore, the modified talc is prepared by the following steps:
[0013] S1. Under nitrogen protection, 3,5-di-tert-butyl-4-hydroxycinnamic acid, 10 wt% sodium hydroxide solution and chloroform were added to a dry three-necked flask, stirred evenly and heated to 60°C, then 3-perfluorooctyl-1,2-epoxypropane was slowly added, and after the addition was completed, the mixture was kept at 60°C for 5 hours. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 1; the dosage ratio of 3,5-di-tert-butyl-4-hydroxycinnamic acid and 3-perfluorooctyl-1,2-epoxypropane was 34.5 g:27.8 mL;
[0014] The molar ratio of 3,5-di-tert-butyl-4-hydroxycinnamic acid and 3-perfluorooctyl-1,2-epoxypropane is controlled to be 1.2-1.3:1, and then 3,5-di-tert-butyl-4-hydroxycinnamic acid and 3-perfluorooctyl-1,2-epoxypropane undergo a ring-opening reaction under heating and base catalysis. The reaction process is as follows:
[0015]
[0016] S2, under nitrogen protection, add intermediate 1, DMAP (4-dimethylaminopyridine) and chloroform into a dry three-necked flask, stir and heat to 50°C, then slowly add a mixed solution of maleic anhydride and chloroform, continue to keep warm at 50°C for 12h after the addition is complete, and distill under reduced pressure after the reaction is completed to obtain intermediate 2; the amount ratio of intermediate 1, maleic anhydride, DMAP and chloroform is 37.6g:5.4g:0.12g:240mL;
[0017] Under the catalytic action of DMAP, the molar ratio of intermediate 1 to maleic anhydride is controlled to be 1:1.05-1.1, and then intermediate 1 and maleic anhydride undergo esterification reaction under heating. The reaction process is as follows:
[0018]
[0019] S3. Under nitrogen protection, add intermediate 2, talcum powder and chloroform into a three-necked flask, mix thoroughly and then slowly add concentrated sulfuric acid. After the addition is complete, heat to 110°C and keep warm for 5 hours. After the reaction is completed, cool to room temperature, filter, wash with deionized water until the filtrate is neutral, and dry at 100°C for 12 hours to obtain modified talcum powder. The dosage ratio of talcum powder, intermediate 2, concentrated sulfuric acid and chloroform is 45g:5g:0.12g:200mL.
[0020] Talc is a hydrous silicate mineral with abundant hydroxyl groups on its surface. The hydroxyl groups react with the carboxyl groups on the surface of the intermediate 2 under the action of concentrated sulfuric acid to produce modified talc.
[0021] Modified talc contains talc, hindered phenol structure and abundant fluorine atoms.
[0022] Talc can increase the viscosity and fluidity of hot melt adhesive, thereby improving its consistency, adhesion and fixation. At the same time, talc can fill the pores and defects in the hot melt adhesive, making the hot melt adhesive smoother when applied on the surface. In addition, talc is a cheap inorganic filler that can effectively reduce the cost of hot melt adhesive. Talc can also adjust the processability of hot melt adhesive and improve its heat resistance.
[0023] Due to its unique structure, the hindered phenol structure can effectively capture free radicals to protect the hot melt adhesive film from oxidative damage. The electronegativity of fluorine atoms is very strong, which can attract electrons to form stable chemical bonds. Therefore, hot melt adhesive films rich in fluorine atoms have excellent water resistance; the radius of fluorine atoms is small, which enables them to form a protective film on the surface of the hot melt adhesive film, tightly covering it and effectively blocking the penetration of water molecules; fluorine atoms have low surface tension, which can significantly reduce the surface energy of the material, making it difficult for water droplets to adhere, thereby achieving a waterproof effect.
[0024] Since the surface of modified talc contains lipophilic ester groups, heterocyclic rings and fluorine-containing long carbon chains, the modified talc has good compatibility with the other organic raw materials of the hot melt adhesive film according to the principle of similar compatibility. At the same time, the surface of modified talc also contains carbon-carbon double bonds, which can react chemically with the unreacted carbon-carbon double bonds at the ends of high-density polyethylene and low-density polyethylene under the action of catalysts, so that the modified talc can be further dispersed and stabilized in the hot melt adhesive film, play a role, and effectively improve the adhesive performance, anti-aging performance and waterproof performance of the hot melt adhesive film.
[0025] Furthermore, the catalyst is one or more of benzoyl peroxide, di-tert-butyl peroxide, and azobisisobutyronitrile.
[0026] A method for preparing a high elastic hot melt adhesive film based on TPR material comprises the following steps:
[0027] Weigh each raw material by weight and put all the raw materials into a mixer to mix evenly, then put them into a twin-screw extruder for melt blending and extrusion granulation; finally, put the granules into a casting machine, cast, cool and shape, to obtain a high-elastic hot-melt adhesive film based on TPR material.
[0028] Beneficial effects of the present invention: modified talc containing talc, hindered phenol structure and rich fluorine atoms has chemical reaction with high-density polyethylene and low-density polyethylene, and has good interface compatibility with other raw materials. In addition, due to the synergistic effect of raw materials such as TPR and tackifying resin, the hot melt adhesive film of the present invention has high elasticity and excellent and stable bonding performance, anti-aging performance and waterproof performance. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1, preparation of modified talcum powder, the specific steps are as follows:
[0031] S1. Under nitrogen protection, 34.5 g of 3,5-di-tert-butyl-4-hydroxycinnamic acid, 43 mL of 10 wt% sodium hydroxide solution and 200 mL of chloroform were added to a 500 mL dry three-necked flask, stirred evenly and heated to 60° C., then 27.8 mL of 3-perfluorooctyl-1,2-epoxypropane was slowly added, and after the addition was completed, the mixture was kept at 60° C. for 5 h. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 1;
[0032] S2, under nitrogen protection, add 37.6g of intermediate 1, 0.12g of DMAP and 220mL of chloroform into a 500mL dry three-necked flask, stir and heat to 50°C, then slowly add a mixed solution of 5.4g of maleic anhydride and 20mL of chloroform, continue to keep warm at 50°C for 12h after the addition is complete, and distill under reduced pressure after the reaction is completed to obtain intermediate 2;
[0033] S3. Under nitrogen protection, add 5 g of intermediate 2, 45 g of talc and 200 mL of chloroform into a 500 mL three-necked flask, mix thoroughly and then slowly add 0.12 g of concentrated sulfuric acid. After the addition is complete, heat to 110°C and keep warm for 5 hours. After the reaction is completed, cool to room temperature, filter, wash with deionized water until the filtrate is neutral, and dry at 100°C for 12 hours to obtain modified talc.
[0034] Example 2: Preparation of a high elastic hot melt adhesive film based on TPR material, the specific steps are as follows:
[0035] Weigh 40 parts of ethylene-vinyl acetate copolymer, 25 parts of high-density polyethylene, 10 parts of low-density polyethylene, 2 parts of TPR, 5 parts of maleic anhydride grafted polyethylene, 5 parts of hydrogenated petroleum resin, 1 part of polyethylene wax, 10 parts of modified talc prepared in Example 1, and 0.01 part of benzoyl peroxide by weight, put all the raw materials into a blender and mix them evenly, then put them into a twin-screw extruder for melt blending and extrusion granulation; finally, put the pellets into a casting machine, cast them, cool and shape them, and obtain a high-elastic hot-melt adhesive film based on TPR material.
[0036] Example 3: Preparation of a high elastic hot melt adhesive film based on TPR material, the specific steps are as follows:
[0037] Weigh 46 parts of ethylene-vinyl acetate copolymer, 29 parts of high-density polyethylene, 14 parts of low-density polyethylene, 4 parts of TPR, 10 parts of maleic anhydride grafted polyethylene, 5 parts of hydrogenated petroleum resin, 5 parts of phenolic terpene resin, 1 part of polyethylene wax, 1 part of methyl silicone oil, 13 parts of modified talc prepared in Example 1, and 0.1 part of di-tert-butyl peroxide by weight, and put all the raw materials into a blender and mix them evenly, then put them into a twin-screw extruder for melt blending, and extrude them into granules; finally, put the granules into a casting machine, cast them, and cool them to shape, so as to obtain a high-elastic hot-melt adhesive film based on TPR material.
[0038] Example 4: Preparation of a high elastic hot melt adhesive film based on TPR material, the specific steps are as follows:
[0039] Weigh 50 parts of ethylene-vinyl acetate copolymer, 35 parts of high-density polyethylene, 15 parts of low-density polyethylene, 5 parts of TPR, 15 parts of maleic anhydride grafted polyethylene, 15 parts of C5 petroleum resin, 3 parts of silicone resin, 15 parts of modified talcum powder prepared in Example 1, and 0.07 parts of azobisisobutyronitrile by weight, put all the raw materials into a blender and mix them evenly, then put them into a twin-screw extruder for melt blending and extrusion granulation; finally, put the pellets into a casting machine, cast them, cool and shape them, and obtain a high-elastic hot-melt adhesive film based on TPR material.
[0040] Comparative Example 1: preparing a hot melt adhesive film, the specific steps are as follows:
[0041] The remaining steps remained unchanged, except that the modified talc in Example 2 was replaced by 9 parts of untreated talc, 0.5 parts of antioxidant 1010, and 0.5 parts of 3-perfluorooctyl-1,2-propylene oxide to prepare a hot melt adhesive film.
[0042] Comparative Example 2, preparing a hot melt adhesive film, the specific steps are as follows:
[0043] The remaining steps remain unchanged, only the modified talcum powder of Example 2 is removed to prepare a hot melt adhesive film.
[0044] Comparative Example 3, preparing a hot melt adhesive film, the specific steps are as follows:
[0045] The remaining steps remain unchanged, only the TPR in Example 2 is removed to prepare a hot melt adhesive film.
[0046] Performance Testing
[0047] The hot melt adhesive films prepared in Examples 2-4 and Comparative Examples 1-3 were subjected to the following performance tests: the bonding strength was tested according to GB / T 2790-1995 (the bonding peel strength requirement between the hot melt adhesive film and metal was ≥50N / 2.5cm; the bonding peel strength requirement between the hot melt adhesive film and the fabric was ≥25N / 2.5cm); dry heat aging was performed at 105°C for 120h, and then the bonding peel strength between the hot melt adhesive film and the metal and the fabric was tested according to GB / T 2790-1995; the contact angle of water on the hot melt adhesive film surface was used to test the waterproof effect of the hot melt adhesive film; the tensile strength was measured according to GB / T2567-2008 standard; the test results of all items are shown in the following table:
[0048]
[0049] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0050] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high elastic hot melt adhesive film based on TPR material, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of ethylene-vinyl acetate copolymer, 25-35 parts of high-density polyethylene, 10-15 parts of low-density polyethylene, 2-5 parts of TPR, 5-15 parts of compatibilizer, 5-15 parts of tackifying resin, 1-3 parts of lubricant, 10-15 parts of modified talc powder, and 0.01-0.1 parts of catalyst; Wherein, the modified talcum powder is prepared by the following steps: S1. Add 3,5-di-tert-butyl-4-hydroxycinnamic acid, 10 wt% sodium hydroxide solution and chloroform into a flask under nitrogen protection, stir and heat to 60°C, add 3-perfluorooctyl-1,2-propylene oxide, react for 5 hours, cool, and distill under reduced pressure to obtain intermediate 1; S2, under nitrogen protection, add intermediate 1, DMAP and chloroform into a flask, stir and heat to 50°C, add maleic anhydride and chloroform, react for 12 hours, and distill under reduced pressure to obtain intermediate 2; S3. Under nitrogen protection, add intermediate 2, talcum powder and chloroform into a flask, add concentrated sulfuric acid after mixing, heat to 110° C. and react for 5 h, cool, filter, wash and dry to obtain modified talcum powder.
2. The high elastic hot melt adhesive film based on TPR material according to claim 1, characterized in that: The usage ratio of 3,5-di-tert-butyl-4-hydroxycinnamic acid and 3-perfluorooctyl-1,2-propylene oxide in step S1 is 34.5 g:27.8 mL.
3. The high elastic hot melt adhesive film based on TPR material according to claim 1, characterized in that: The usage ratio of the intermediate 1, maleic anhydride, DMAP and chloroform in step S2 is 37.6 g:5.4 g:0.12 g:240 mL.
4. The high elastic hot melt adhesive film based on TPR material according to claim 1, characterized in that: The usage ratio of talcum powder, intermediate 2, concentrated sulfuric acid and chloroform in step S3 is 45g:5g:0.12g:200mL.
5. The high elastic hot melt adhesive film based on TPR material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polyethylene.
6. The high elastic hot melt adhesive film based on TPR material according to claim 1, characterized in that: The tackifying resin is one or more of hydrogenated petroleum resin, phenolic terpene resin and C5 petroleum resin.
7. The high elastic hot melt adhesive film based on TPR material according to claim 1, characterized in that: The lubricant is one or more of polyethylene wax, methyl silicone oil and silicone resin.
8. The high elastic hot melt adhesive film based on TPR material according to claim 1, characterized in that: The catalyst is one or more of benzoyl peroxide, di-tert-butyl peroxide and azobisisobutyronitrile.
9. The method for preparing a high elastic hot melt adhesive film based on TPR material according to claim 1, characterized in that: The following steps are involved: Weigh each raw material by weight and put all the raw materials into a mixer to mix evenly, then put them into a twin-screw extruder for melt blending and extrusion granulation; finally, put the granules into a casting machine, cast, cool and shape, to obtain a high-elastic hot-melt adhesive film based on TPR material.
Citation Information
Patent Citations
Hot melt adhesive film composition as well as preparation method and application thereof
CN114369426A
Antibacterial environment-friendly tableware material and preparation method thereof
CN118813017A